Concordance between in vivo reflectance confocal microscopy and optical histology of lymphomatoid papulosis. Issue 3 (26th February 2013) - Ardigò, Marco; Donadio, Carlo; Vega, Hernando; Cota, Carlo; Moscarella, Elvira; Agozzino, Marina
<x xml:space="preserve">Abstract</x> Background Lymphomatoid papulosis is a primary cutaneous CD30+ T‐cell lymphoma clinically characterized by a benign, chronic, recurrent course with self‐limited papulo‐nodular skin lesion eruption. In vivo Reflectance Confocal Microscopy is a non‐invasive technique for real‐time imaging of the superficial layers of the skin down to the superficial dermis with cellular‐level resolution close to conventional histopathology. RCM has been previously reported to be useful in the in vivo evaluation of inflammatory diseases, skin tumours and also cutaneous lymphomas. Only two articles have been published on cutaneous lymphomas and none detailing confocal features of LyP. The aim of this manuscript was to describe the confocal features of LyP and their histological correlation to evaluate the possible application of this non‐invasive tool in this T‐cell lymphoma subtype clinical management. Methods Five patients with histological diagnosis of LyP were imaged with RCM, followed by a skin biopsy on a clinically selected lesion. Results High grade of correspondence between RCM and histopathology of LyP was observed, disclosing the potential rule of RCM at least for biopsy site selection. Conclusion Future studies on RCM for LyP vs. other cutaneous T‐cells lymphomas and inflammatory skin diseases are needed to assess specificity and sensibility of our preliminary data.